Peer Victimization and Mental Health Risk in Chilean Students - Bilbao-Ramirez, M (Springer New York LLC, 2018)
Children who exhibit mental health problems are more likely to be targets of peer victimization. However, little is known about how mental health risk interacts with other individual and school-level factors in this relationship. In the current study, we explored the associations between peer victimization and mental health in 10,532 Chilean sixth grade students attending 405 of the lower SES schools in the country. Children were screened for mental health and classroom adaptation problems using standardized parent and teacher rating scales at the beginning of the school year, and completed questionnaires on self-reported peer victimization, classroom climate, and school climate at the end of the year, as part of an ongoing national school mental health program, which includes monitoring for school violence and school climate. Data were analyzed through logistic regression and multilevel analyses, incorporating sex, absenteeism due to physical health, school attendance, and individual SES as covariates. Results showed that the odds of being victimized by peers were five times greater for students who were identified at risk for mental health problems based on parent reports, and one time greater for students identified by teachers with attention and concentration difficulties. However, multilevel analyses showed that the relative contribution of mental health risk to peer victimization significantly diminished when other individual and school-level variables were included. Particularly relevant was the contribution of individual SES, classroom climate, and absenteeism due to physical health; and of school-level SES. These findings suggest the complex nature of the influence of mental health on peer victimization and the relevance of the social context interacting with student’s mental health problems. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.